E-JUSTICE: theoretical principles and problems of realization of the right to judicial protection in the conditions of digitalization - Миколенко, Олександр Іванович; Миколенко, О. І.; Миколенко, Александр Иванович; Mykolenko, Oleksandr I.; Дрішлюк, Володимир Ігорович; Дрішлюк, В. І.; Дришлюк, Владимир Игоревич; Drishliuk, Volodymyr I.; Волкова, Наталія Василівна; Волкова, Н. В.; Волкова, Наталия Васильевна; Volkova, Nataliia V.; et al. (IJCSNS, 2021)
The article deals with the peculiarities of the realization by citizens of the constitutional right to judicial protection in the conditions of digitalization. The purpose of the article was to establish the state of implementation of "e-justice" and to analyze the features of e-justice in Ukraine and abroad. In particular, in October 2021, Ukraine will have a full-fledged e-justice system, which includes all the necessary elements of justice, from filing a claim in electronic form and ending with the consideration of the case by videoconference. To carry out scientific research, the authors used some methods, among which are the methods of induction, deduction, hermeneutic, comparative analysis, and formal-legal method. The authors of the article concluded that the process of introduction of the e-justice system in the world is irreversible and necessary. It is gratifying that Ukraine is in the rear of the developed world in this context. The coming months will provide grounds for interim conclusions on the quality of domestic e-justice. However, proper scientific understanding of e-court issues, taking into account the significant experience of e-justice in European countries and the work of the domestic Ministry of Digital Transformation, will undoubtedly make it possible to bring Ukrainian e-justice to the proper functional level. Further research will assist in this.

У статті розглядаються особливості реалізації громадянами конституційного права на судовий захист в умовах цифровізації. Метою статті було встановити стан впровадження «електронного правосуддя» та проаналізувати особливості електронного правосуддя в Україні та за кордоном. Зокрема, у жовтні 2021 року в Україні з’явиться повноцінна система електронного правосуддя, яка включає всі необхідні елементи правосуддя, починаючи від подання позову в електронній формі і закінчуючи розглядом справи у режимі відеоконференції. Для проведення наукового дослідження автори використали методи, серед яких методи індукції, дедукції, герменевтичний, порівняльний аналіз, формально-правовий метод. Автори статті дійшли висновку, що процес впровадження системи електронного правосуддя у світі є незворотнім і необхідним. Приємно, що Україна в цьому контексті знаходиться в тилу розвиненого світу. Найближчі місяці дадуть підстави для проміжних висновків щодо якості внутрішнього правосуддя. Однак належне наукове осмислення питань електронного суду, враховуючи значний досвід електронного правосуддя в європейських країнах та роботу вітчизняного Міністерства цифрової трансформації, безсумнівно, дасть змогу вивести українське електронне правосуддя до належного функціонального рівня. У цьому допоможуть подальші дослідження.
Mykolenko O. E-JUSTICE: theoretical principles and problems of realization of the right to judicial protection in the conditions of digitalization / O. Mykolenko, V. Dryshliuk, N. Volkova, V. Prytuliak, O. Verba // International Journal of Computer Science and Network Security. - Vol. 21. - № 10. - IJCSNS, 2021. - Р. 295-301.
Keywords: e-justice; justice; e-court; digitization; right to judicial protection; електронне правосуддя; правосуддя; електронний суд; оцифрування; право на судовий захист; Research Subject Categories::LAW/JURISPRUDENCE